Transcriptional Regulation of Δ6-Desaturase by Peroxisome Proliferative-Activated Receptor δ Agonist in Human Pancreatic Cancer Cells: Role of MEK/ERK1/2 Pathway - Maryam Darabi; Shima Byagowi; Shabnam Fayezi; Masoud Darabi; Shahab Mirshahvaladi; Mehdi Sahmani (The Scientific World Journal)
The Δ6-desaturase (Δ6D), also known as fatty acid desaturase 2, is a regulatory enzyme in de novo fatty acid synthesis, which has been linked to obesity and diabetes. The aim of the present study was to investigate the effect of peroxisome proliferative-activated receptor δ (PPARδ) agonist and MEK/ERK1/2-dependent pathway on the expression of Δ6D in human pancreatic carcinoma cell line PANC-1. PANC-1 cells cultured in RPMI-1640 were exposed to the commonly used ERK1/2 pathway inhibitor PD98059 and PPARδ agonist GW0742. Changes in mRNA and protein expression of Δ6D were then determined using real-time RT-PCR and Western blot, respectively. The expression of Δ6D (P<0.01) increased following treatment with PPARδ agonist both at mRNA and protein levels, whereas no significant change was observed after treatment with MEK/ERK1/2 pathway inhibitor. It was also found that the increase in the expression of Δ6D in response to GW0742 was significantly inhibited by PD98059 (>40%, P<0.05) or EGF receptor-selective inhibitor AG1478 (>25%, P<0.05) pretreatment. PPARδ and MEK/ERK1/2 signaling pathways affect differentially the expression of Δ6D in pancreatic cancer cells. Furthermore, there may be an inhibitory crosstalk between these two regulatory pathways on the mRNA expression of Δ6D and subsequently on Δ6D protein expression.